Psoriasis and sleep disorders: A systematic review. (October 2016) - Gupta, Madhulika A.; Simpson, Fiona C.; Gupta, Aditya K.
Summary: Psoriasis is an immune-mediated chronic inflammatory disorder which manifests as dermatologic lesions, and psoriatic arthritis (PsA) in about 30% of cases. Psoriasis is associated with multiple comorbidities including metabolic syndrome, hypertension, diabetes, cardiovascular events, obesity and psychiatric disorders, which can all affect the course of sleep disorders. A systematic review of the literature on the relationship between psoriasis, PsA, and formal sleep disorders identified 33 studies. There is an increased prevalence of obstructive sleep apnea (OSA) with 36%–81.8% prevalence in psoriasis versus 2%–4% in the general population. There was also an increase in the prevalence of restless legs syndrome of 15.1%–18% in psoriasis versus 5%–10% in European and North American samples. The wide variety of insomnia criteria used in studies resulted in an insomnia prevalence of 5.9%–44.8% in psoriasis, which is insufficient to show an elevated prevalence when the general population has a 10% prevalence of chronic insomnia and 30–35% prevalence of transient insomnia. There is evidence that symptoms of insomnia in psoriasis are directly mediated by pruritus and pain. Treatments that decrease the cutaneous symptoms in psoriasis were successful in mitigating insomnia, but did not show improvements in OSA where the relationship with psoriasis is multifactorial.